BRAND IMAGE ATLET MOTO GP SEBAGAI ENDORSER YAMAHA NMAX TERHADAP KEPUTUSAN PEMBELIAN CUSTOMER DI KOTA BANDUNG - RISA RATNA GUMILANG (Coopetition : Jurnal Ilmiah Manajemen, 2019)
Various motorcycle manufacturers competing to meet the needs of the market, carrying a variety of company’s motorcycle trying to serve two-wheeler market by offering a wide range of product variants. Basic scientific work is to introduce the influence of Valentino Rossi as a Atlet Moto GP endorser and brand image on purchasing decisions Yamaha NMAX in Bandung. The scientific work focuses on the study of Bandung through data analysis technique multiple linear regression inclusion of samples obtained were 108 respondents using purposive sampling. Data to answer with the help of SPSS program proves Atlet Moto GP endorser and the brand image simultaneously influence on purchasing decisions Yamaha NMAX in Bandung.